Milk composition and blood metabolic profile from holstein cows at different calving orders and lactation stages - Dias, Mariana Borges de Castro; Leão, Karen Martins; Carmo, Ruthele Moraes do; Silva, Marco Antônio Pereira da; Nicolau, Edmar Soares; Marques, Thaisa Campos (Acta Scientiarum. Animal Sciences, 2017)
This study aimed to evaluate milk composition and metabolic profile of Holstein cows at different calving orders in the beginning, middle, and end of lactation. One hundred ten Holstein cows were housed in a free stall system receiving the same diet and were grouped according to calving order (first, second, third, and fourth calving) and days in milk (DIM): early (1-90 DIM), middle (91-180 DIM), and end of lactation (over 181 DIM) for comparing milk yield, milk composition, and blood metabolic profile between the calving orders within the same lactation period. These parameters were also evaluated between lactation periods of the cows in different calving orders. The calving order, in any lactation stage, had no influence on milk yield per day and blood biochemical profile of Holstein cows receiving the same diet. However, calving order in all stages of lactation influenced milk composition. The first, second, third, and fourth calving order had no effect on the blood biochemical profile of Holstein cows, in any lactation stage. On the other hand, the different stages of lactation influenced milk yield and milk composition of Holstein cows.